2016
DOI: 10.1353/hpu.2016.0081
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Use for Dental Problems among Homeless Individuals: A Population-Based Cohort Study

Abstract: Objectives-To evaluate emergency department (ED) visits for dental problems among Toronto's homeless population (Ontario, Canada).Methods-A random sample of 1,189 homeless was recruited from shelters and meal programs. Emergency department visits for non-traumatic dental problems (ICD-10-CA codes K00-K14) were identified using participants' health insurance number, during [2005][2006][2007][2008][2009]. Age-and sexmatched controls were selected from low-income neighborhoods.Results-Homeless and matched control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 15 publications
1
38
0
Order By: Relevance
“…14 Studies have shown that DPAT addressed within 24 hours will prevent poor prognosis and subsequent dentalrelated issues. 11 An important finding in the present study is that 4772 patients had two or more visits for DPAT. Expansion of dental public health services should be a viable cost-effective solution to address the dental needs of the population.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…14 Studies have shown that DPAT addressed within 24 hours will prevent poor prognosis and subsequent dentalrelated issues. 11 An important finding in the present study is that 4772 patients had two or more visits for DPAT. Expansion of dental public health services should be a viable cost-effective solution to address the dental needs of the population.…”
Section: Discussionmentioning
confidence: 54%
“…10 The availability of dental services without the barrier of affordability will facilitate access to dental professionals and possibly reduce the inappropriate utilization of EDs for dental problems. 11 An important finding in the present study is that 4772 patients had two or more visits for DPAT. The quantitative nature of this study does not provide qualitative findings on the repeated EDs visits.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…7 Yet, in Canada, most studies on ED visits for NTDC present data for only one or two years; 4,5 only one has presented trend data, but it was limited to homeless adults over a four-year period in one Ontario municipality. 3 Trend data are important, as they give researchers and policy-makers the ability to explore patterns in a given outcome, and allow for hypothesis formulation on potential environmental exposures and their effects on such trends. Further, though most studies on ED visits for NTDC in Canada quantify the burden, they do not report on the predictors of such visits either at the individual or area-based level.…”
mentioning
confidence: 99%